Perancangan Sistem e-Office Berbasis Web Menggunakan Framework Laravel untuk Digitalisasi Manajemen Persuratan Biro Kesejahteraan Rakyat - M. Irdan Aljibran; Gusmelia Testiana (Journal of Information Systems and Business Technology, 2026)
The People's Welfare Bureau of the Regional Secretariat of South Sumatra Province still manages correspondence administration manually using agenda books and physical disposition sheets. This approach creates several challenges, including the risk of document loss, delays in delivering dispositions, difficulties in tracking correspondence history, the absence of real-time task monitoring, and inconsistencies in outgoing letter numbering. This study aims to design and develop a web-based correspondence management information system called e-Office Kesra as part of the Satu Data Sumatera Selatan Batch 2 Internship Program 2026. The system was developed using the Laravel framework with the Model-View-Controller (MVC) architecture, Blade Templating Engine, Tailwind CSS, and a MySQL database. The Waterfall development model was applied, consisting of requirements analysis, system design, implementation, and functional testing. The system implements Role-Based Access Control (RBAC) with three user roles: Administrative Officer, Manager, and Staff. Its main features include incoming mail management, digital disposition with real-time status monitoring, multi-level approval for outgoing correspondence, and automatic official letter numbering. Black-box testing results indicate that all system functions operate as expected without critical functional errors. The e-Office Kesra system effectively digitizes correspondence administration and supports the digital transformation of government services in accordance with Indonesia's One Data policy.